Flying Activity of Apis cerana Honey Bee at Surouding Hive Area in Central Sulawesi - I Made Budiarsa; Masrianih; Fatmah Dhafir; Manap Trianto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Information on foraging activity is important for efforts to increase the productivity of Apis cerana honeybees. Honey bees flying activities are carried out in the context of nest guarding activities from enemy attacks, removing feces from the nest, and foraging which takes place during the day to collect pollen and nectar from plants. This study aims to analyze the daily activity patterns of bees A. cerana which is influenced by environmental factors. This study used two colonies of A. cerana, namely colony one and colony two with the same colony size. The observed behaviors were bees leaving the nest, entering with pollen, and entering without pollen. The number of A. cerana colony one flying for pollen was high in the morning and low in the afternoon due to the very high light intensity during the day. Unlike colony one, A. cerana colony two did not actively perform flight activities and showed a different activity of flying in front of the nest forming a crowd in the afternoon. An inflorescence calendar needs to be developed to determine the flowering period of plants around the hive so that bee forage is continuously available to avoid absconding. absconding. Identification of plant pollen as a source of bee food needs to be done to determine the types of plants utilized by bees.